Symposium 7: An overview of design representations - Conole, Gráinne (Proceedings of the International Conference on Networked Learning, 2010)
This paper provides an overview of the range of representations that can be used to describe learning designs. It provides a definition for learning designs and demonstrates how the different representations can be used for different levels of granularity and to foreground different aspects of the design process.